



 
If a is proportional to b then a = kb for some constant k. (lets consider only a,b,k nonzero). Then a^{2}b^{2} = (kb)^{2}  b^{2} = (k^{2}1)b^{2} and ab = (kb)b=kb^{2}. Thus (a^{2}  b^{2}) / ab = (k^{2}1)b^{2}/(kb^{2}) = (k^{2}1)/k which is a constant, Thus if a is proportional to b then a^{2}b^{2} is proportional to ab (for b not equal to zero). Thx,
Hello Nazrul, Let m = (k^{2}  1)/k then a^{2}  b^{2} = m ab. Thus a^{2}  b^{2} is proportional to ab. Tyler  


Math Central is supported by the University of Regina and The Pacific Institute for the Mathematical Sciences. 